Access to water, sanitation and hygiene (WASH) services and drinking water contamination risk levels in households of Bishoftu Town, Ethiopia: A cross-sectional study - Girmay, A.M.; Mengesha, S.D.; Dinssa, D.A.; Alemu, Z.A.; Wagari, B.; Weldegebriel, M.G.; Serte, M.G.; Alemayehu, T.A.; Kenea, M.A.; Weldetinsae, A.; Teklu, K.T.; Adugna, E.A.; et al. (Wiley, 2023)
Background and Aims Access to safe drinking water, sanitation, and hygiene is a fundamental human right and essential to control infectious diseases. However, many countries, including Ethiopia, do not have adequate data to report on basic water, sanitation, and hygiene (WASH) services. Although contaminated drinking water spreads diseases like cholera, diarrhea, typhoid, and dysentery, studies on drinking water contamination risk levels in households are limited in Ethiopia. Therefore, closing this gap needs investigation.